Resposta ecológica de besouros scarabaeinae (Coleoptera: Scarabaeidae) a diferentes usos do solo na Amazônia Oriental - Silva, Kaires Mayane Araújo da (2022)
Few studies relate the effects of replacing native forests with other anthropogenic ecosystems, such as pastures, agriculture, selective logging, fragmentation and forestry, on the composition of Scarabaeinae communities in the Amazon. Given this, it is essential to understand the response of ecological indicators to assess the changes in progress. Thus, the objective of this research was to evaluate the ecological responses of Scarabaeinae communities to land use modification in the Eastern Amazon. For this, collections were carried out in preserved vegetation, secondary vegetation, eucalyptus plantations and pastures. The collection technique was pitfall traps, baited with human feces, banana molasses, putrefying meat and unbaited traps that served as controls. The following hypotheses were raised: there is a loss of Scarabaeinae diversity with changes in land use (eucalyptus plantations, pasture and secondary vegetation compared to areas of primary vegetation) and; that preserved forests maintain unique species when compared to degraded environments. The results showed that the abundance and richness of species varied significantly between the different environments, namely, between the most preserved environments compared to the degraded ones. It was also identified that the composition was different between the environments, with a clear separation between the different environments by ordering the species composition, with a small overlap between more preserved vegetation and secondary vegetation. The greatest abundance and richness of beetles was observed in the pitfall trap with feces bait. The results provide evidence that structurally more complex environments harbor greater abundance, richness and composition of Scarabaeinae.